Slowdown of group velocity of light in dual-frequency laser-pumped cascade structure of Er3+-doped optical fiber at room temperature. (22nd February 2018) - Qiu, Wei; Yang, Yujing; Gao, Yuan; Liu, Jianjun; Lv, Pin; Jiang, Qiuli
Abstract: Slow light is demonstrated in the cascade structure of an erbium-doped fiber with two forward propagation pumps. The results of the numerical simulation of the time delay and the optimum modulation frequency complement each other. The time delay and the optimum modulation frequency depend on the pump ratio G ( G   =   P 1480 : P 980 ). The discussion results of this paper show that a larger time delay of slow light propagation can be obtained in the cascade structure of Er 3+ -doped optical fibers with dual-frequency laser pumping. Compared to previous research methods, the dual-frequency laser-pumped cascade structure of an Er 3+ -doped optical fiber is more controllable. Based on our discussion the pump ratio G should be selected in order to obtain a more appropriate time delay and the slowdown of group velocity.